Studi Penambatan Maya dan Prediksi Toksisitas Turunan 5-Fluorouridin Monofosfat Pada Enzim Orotidin-5-monofosfat Dekarboksilase - Andzar Fikranus Shofa; Anggie Fuji Lestari; Hafidh Agrestian Soputri; Kharisma Safenti (Pharmaceutical and Biomedical Sciences Journal (PBSJ), 2022)
Cancer is one of the leading causes of death in the world. Various cancer treatments had undergone many developments, one of which is through the process of drug discovery of cancer drugs. 5-Fluorouridine Monophosphate is a potential active metabolite of 5-fluorouracil and the ligand for the enzyme Orotidine-5-monophosphate decarboxylase (OMPD), so it deserves further development through structural modification. This study aims to predict the cytotoxic activity and toxicity of the parent compound 5-Fluorouridine Monophosphate and twenty derivative compounds as candidates for anticancer drugs. The mechanism of action of 5-Fluorouridine Monophosphate derivatives as anticancer by inhibiting OMPD, a carboxylation enzyme that is important in nucleotide biosynthesis in the process of cellular replication. Biological activity was predicted through molecular modeling called in silico assay using the Molegro Virtual Docker (MVD) program, while compound toxicity was predicted using the pkCSM online tools program. The in silico test is carried out by docking the compound whose activity will be predicted against the OMPD receptor target with the code PDB. 2QCF. The results of docking in the form of bond energy are indicated by the value of the Rerank Score (RS). Compounds that have a small RS value are predicted to have more stable ligand-receptor binding and have high activity. Based on the results of the in silico test, it can be concluded that all derivatives of 5-Fluorouridine Monophosphate meet the requirements of Lipinski's law. Then the results of molecular docking showed that the RS value of the derivative compound number 16 was lower than the parent compound 5-Fluorouridine Monophosphate, but had more hydrogen bonds with amino acid residues than the parent compound. Therefore, it can be concluded that the 16th derivative with the formula C16H25F2N2O7P is the most feasible to be synthesized and continued by testing its activity in vitro and in vivo.